IMPLEMENTASI PROGRAM AIR BERSIH BADAN USAHA MILIK DESA SUMBER SARI DI DESA KALISARI KABUPATEN BANYUMAS - Faiqotunnisa, Arina; Sutikno, Chamid; Ayu Permana Pribadi, Indah; Amanda, Ariesta; Nastiti, Dian (Jurnal Inovasi Daerah, 2024)
The purpose of this study is to describe the implementation process of the clean water program in Kalisari Village, Cilongok District, Banyumas Regency. This study uses a descriptive method with a qualitative approach, to describe in general a problem in the research conducted. The results of the study indicate that the implementation of the clean water program managed by BUMDes Sumber Sari in Kalisari Village, Cilongok District, Banyumas Regency in terms of communication has been running well and is running stably and developing. It’s proven by improving program and following up on complaints from residents that have been conveyed. In terms of resources, the potential resources owned are utilized as an effort to achieve success in the program. In terms of disposition, the program is running very well, as evidenced by the satisfaction of employees in the distribution of incentives and appreciation given. In terms of bureaucratic structure, the program is running well, as evidenced by the division of structures that are given tasks and responsibilities to those who are experts in their fields and have clear SOPs to be used as guidelines so that the program runs effectively.